STRATEGI KEPALA MADARASAH DALAM PELAKSANAAN PROGRAM BACA KITAB KUNING DI MASA PANDEMI COVID-19 (Studi Kasus Madrasah Diniyah Mafatihun Naja Munggut Padas Ngawi) - Nur Hidayah (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2021)
Currently, both formal and non-formal educational institutions are affected by the COVID-19 pandemic, including at Madrasah Diniyah Mafatihun Naja Munggut. This condition is a challenge for the Head of Madrasah in preparing strategies for effective education. This study aims to find out how the strategy of the head of Madrasah Diniyah Mafatihun Naja Munggut in the implementation of the Kitab Kuning reading program during the covid-19 pandemic and the supporting and inhibiting factors. The approach and type in this research is descriptive qualitative. The results of this study were the strategy adopted by the Head of Madrasah to implement a shift system, always comply with health protocols, reduce activities that caused crowds, urge all Asatidz councils to make exam questions according to the material that had been taught. The supporting factor is getting full support from the guardians of the students and the surrounding community, the high enthusiasm for learning arises from the students themselves. The inhibiting factor is the limited time to complete the material, when entering among the students, they have forgotten the material that has been studied.